Factor Analysis of the Incidence of Infertility in Couples of Childbearing Age at the Dagifa Medical Center Clinic - Arsenia Lolonlun; Nofa Anggraini (Sean Institute, 2023)
The prevalence of infertility in Indonesia is currently 12-15% of the 40 million couples of childbearing age who experience problems in fertility. Every married couple or couple of childbearing age after marriage will want to have offspring (have children). However, couples of childbearing age are unable to conceive for 12 months with frequent sexual intercourse 2-3 times a week. The purpose of this study was to analyze the factors of infertility in couples of childbearing age at the dagifa medical center clinic. This research is a type of observational analytic research cross sectional design with a quantitative approach. The research was conducted at the Dagifa Medical Center Clinic in December 2022. The research sample was total sampling, namely all couples of childbearing age recorded in medical records in January - November 2022 with a total of 45 people. The instrument used in the form of a questionnaire sheet consisting of repsonden biodata and a statement sheet about factors that influence the incidence of infertility. Univariate analysis using the frequency distribution formula, namely the variable characteristics of respondents. In bivariate analysis using SPSS chy-square test. There is a relationship between age, nutritional status and menstrual cycle with the incidence of infertility in couples of childbearing age at the Dagifa Medical Center Clinic in 2022 because the p-value of each with the acquisition of 0.00 <0.05. so it is advisable for health workers especially midwives to provide information related to infertility in couples of childbearing age so that they can provide prevention and direction if there is one of the factors in the current study